ANALYSIS OF WORD FORMATION - Jalilova Rayhona Sherzod qizi; Xayrilloyeva Aziza Olimjon qizi; Zaripova Aziza Shaxobiddinova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article provides a comparative analysis of the process of affixation, one of the important methods of word formation in Uzbek and English. The main goal of the study is to identify the similarities and differences of affixation in the two language systems.During the study, selected lexical units from Uzbek and English were morphologically analyzed.